Nexus between Customer Expectation and E-Purchase Intention: Exploring the Role of Perceived Justice (KASBIT Business Journal, 2020)
This study focuses on the factors influencing the customer purchase trends through online shopping in presence of moderation of perceived justice. The study fills the gap by integrating two theories unified theory of acceptance and use of technology (UTAUT2) and perceived justice theory as underpinning theories. An established questionnaire was used to collect primary responses from 384 users of online cab booking service. Data have been analyzed through partial least squares structural equation modeling (PLS-SEM) approach by using Smart PLS software. Results revealed that from customer’s expectation factors, effort expectancy (EE), performance expectancy (PE) and perception of trust (PT) has found a substantial impact on individual’s purchase intention (PI), which further affects perceived behavior (PB). It also revealed that most important customer’s expectation factors can help the brands to tackle customer’s mindset. Practically this study also provides a guideline for service sector to train their frontline employees because in service sector behavior of service deliver personal is most important factor. This is a rare study which explores the nexus between customer expectation and e-purchase intention in online cab booking service. It also extends conceptualization of UTAUT2 with exploring the role of perceived trust and moderation of perceived justice.
Keywords: Effort Expectancy; Performance Expectancy; Perceived Justice; Distributive Justice; Procedural Justice; Interactional